2011
DOI: 10.21608/bfsa.2011.63273
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Pattern of Galectin-3 in the Rat Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third most frequent cause of cancer death world wide, with an estimated mortality rate of about one million deaths annually. Galectin-3 is widely spread among different types of cells and tissues. Galectin-3 found intracellularly in nucleus and cytoplasm. Galectin-3 affects numerous biological processes and seems to be involved in different physiological and pathophysiological conditions, such as development, immune reactions, and neoplastic transformation and metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Based on previous findings, we can conclude that neither serum galectin-3 nor MMP-9 is useful as a tumor marker for the diagnosis of HCC, since it is well known that HCC is frequently associated with liver cirrhosis and a major function of a tumor marker is that the marker should be able to differentiate patients who truly have cancer from those who do not, especially that early detection of HCC is mainly carried out in hepatic patients. However, Galectin-3 might be a potential therapeutic target for the prevention and treatment of HCC; this was in consistency with Liu and Rabinovich, 45 Nangia-Makker, 42 and Mohafez 46 where animal experiments by Liu 47 found that blocking galectin-3 function could effectively inhibit the growth of colon cancer liver metastasis.…”
Section: Discussionsupporting
confidence: 76%
“…Based on previous findings, we can conclude that neither serum galectin-3 nor MMP-9 is useful as a tumor marker for the diagnosis of HCC, since it is well known that HCC is frequently associated with liver cirrhosis and a major function of a tumor marker is that the marker should be able to differentiate patients who truly have cancer from those who do not, especially that early detection of HCC is mainly carried out in hepatic patients. However, Galectin-3 might be a potential therapeutic target for the prevention and treatment of HCC; this was in consistency with Liu and Rabinovich, 45 Nangia-Makker, 42 and Mohafez 46 where animal experiments by Liu 47 found that blocking galectin-3 function could effectively inhibit the growth of colon cancer liver metastasis.…”
Section: Discussionsupporting
confidence: 76%
“…Gal-3 also plays a tumor promotion role in the proliferation of cancers cells. Gal-3 can increase cell growth of hepatocellular carcinoma [ 40 ], glioma cells [ 41 ], pancreatic cancer proliferation, The effects of Gal-3 on the cell proliferation and cycle came about as a result of the translocation ability of Gal-3 into the nucleus by binding with Impotin, Sufu, and Nup98, wherein it controls the cell cycle through the interaction with cyclin A, cyclin D, cyclin E, p21 (WAF1), and p27 (KIP1), accelerating cancer cell proliferation [ 42 ]. Studies performed on diverse cell types, mostly cancerous cell lines, have demonstrated that galectin-7 has a suppressive effect on cell proliferation.…”
Section: Galectins In Cancermentioning
confidence: 99%